Implementation of independent learning campus independent certified internship program for strengthening 21st century skills - Lestari, Desi Ayu; Sutrisno, Sutrisno; sulton, sulton (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2024)
Implementation of the Merdeka Belajar Campus Merdeka Certified Internship Program in Strengthening 21st Century Skills is a way to strengthen skills in using media information as well as career and life skills. The aim of this research is to; (1) Describe the implementation of the MBKM certified internship program in universities, (2) Describe the mastery of 21st century skills among students participating in certified internships. This research is qualitative research with an analytical study approach. The results of this research show that first, in the implementation of MBKM, the certified internship program was implemented in three areas of activity, namely marketing, finance and operations, both in banking and companies. In implementing a certified internship, there are several stages, namely conversion of 20 credits, internship activities for 18 weeks, experience in the world of work and the professional world, a series of skills, mentoring, and obtaining a certificate of recognition for the skills and experience gained. Apart from that, during the implementation of the certified internship program there is an evaluation. Evaluation is carried out by following up on reports, providing mentoring, checking recaps of internship activities, sharing lessons, and conducting a final assessment of student performance. Second, the mastery of 21st century skills by students participating in certified internships focuses on the skills of mastering the use of technology, including the use of marketplace applications, the use of Microsoft office applications, the use of e-learning systems, e-commerce, design and so on. Meanwhile, mastery of career abilities and life skills is carried out through strengthening adaptation and social abilities, productivity and accountability, and providing leadership abilities and responsibility